1995
DOI: 10.1126/science.7638625
|View full text |Cite
|
Sign up to set email alerts
|

Object-Centered Direction Selectivity in the Macaque Supplementary Eye Field

Abstract: Object-centered spatial awareness--awareness of the location, relative to an object, of its parts--plays an important role in many aspects of perception, imagination, and action. One possible basis for this capability is the existence in the brain of neurons with sensory receptive fields or motor action fields that are defined relative to an object-centered frame. In experiments described here, neuronal activity was monitored in the supplementary eye field of macaque monkeys making eye movements to the right o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(131 citation statements)
references
References 23 publications
3
124
4
Order By: Relevance
“…One explanation for this pattern is that they indicate involvement in response preparation and/or execution. Indeed, the frontal eye field and supplementary eye field have been found to play crucial roles in the planning of voluntary eye movement responses based on single-cell and neuroimaging studies (e.g., Chen and Wise, 1995;Curtis, 2006;Funahashi et al, 1991Funahashi et al, , 1989Hanes et al, 1995;Schall, 1991;Mann et al, 1988;Olson and Gettner, 1995;Schlag and Schlag-Rey, 1987;Tehovnik et al, 2000). Based on the patterns in the time courses and consideration of the timing of the components of the ODR trials, our results provide additional evidence that these regions play a role in response preparation.…”
Section: Discerning Functional Roles Based On Differences In the Timementioning
confidence: 56%
“…One explanation for this pattern is that they indicate involvement in response preparation and/or execution. Indeed, the frontal eye field and supplementary eye field have been found to play crucial roles in the planning of voluntary eye movement responses based on single-cell and neuroimaging studies (e.g., Chen and Wise, 1995;Curtis, 2006;Funahashi et al, 1991Funahashi et al, , 1989Hanes et al, 1995;Schall, 1991;Mann et al, 1988;Olson and Gettner, 1995;Schlag and Schlag-Rey, 1987;Tehovnik et al, 2000). Based on the patterns in the time courses and consideration of the timing of the components of the ODR trials, our results provide additional evidence that these regions play a role in response preparation.…”
Section: Discerning Functional Roles Based On Differences In the Timementioning
confidence: 56%
“…It has been known for a long time that each hemisphere of the human brain preferentially processes contralateral egocentric spatial information (Tootell et al, 1982). Recently, it has been found that supplementary eye field neurons coding object-centered direction of saccades were distributed mainly in the contralateral hemisphere (Olson and Gettner, 1995), which indicated that each hemisphere mainly processed contralateral allocentric representation (Olson and Gettner, 1996).…”
Section: Hemispheric Asymmetry In Egocentric Processingmentioning
confidence: 99%
“…Chen and Wise also suggested that the SEFs are part of a neural system "learning flexible, non-spatial stimulus-response relations" (p. 1101). Further evidence for object-centered response properties of neurons in the SEFs comes from single-cell recordings by Olson and Gettner (1995, 1999. They found SEF neurons that were activated most strongly when the animals were preparing saccadic eye movements to particular locations on a stimulus, irrespective of its absolute position.…”
Section: Possible Neural Correlatesmentioning
confidence: 99%